Escolas em Foco: The assessment of the impact of an ’evidence-based public policies’ program of the municipal education network of Rio de Janeiro - Andrade, Felipe Macedo de; Ceneviva, Ricardo; Koslinski, Mariane C. (Education Policy Analysis Archives, 2022)
The paper assesses the impact of a data use program on student’s educational achievement in language and math in public schools in Rio de Janeiro, Brazil. The idea behind this kind of program is based on the perspective that interventions aimed to encourage the use of educational data for planning and pedagogical activities would result in changes in the attitudes, knowledge, and practices of school agents and, therefore, would contribute student achievement and the reduction of inequalities. The impact of the program was examined using a differences-in-differences statistical models (DiD). The first analysis strategy did not have any pre-processing mechanism, and for the second strategy, to reduce bias selection and increase the power of causal inference, the matching method was adjusted before DiD model. Although descriptive statistics suggests constant increase in student academic performance both in mathematics and language and school retention rates of both groups over four years of analysis, the results suggest both strategies are substantively weak and not statistically significant.